(untitled) (Prithvi Academic Journal, 2026)
This study examined the relationship between emotional intelligence (EI) and self-efficacy (SE) among post-graduate students. A total of 272 participants were selected through convenience sampling, and data were collected using self-administered structured questionnaires measuring EI and SE. Structural equation modeling (SEM) with the weighted least squares mean and variance (WLSMV) technique was employed to investigate the associations between four dimensions of EI and SE. Findings indicate that others’ emotional appraisal (OEA) and regulation of emotions (ROE) were positively related to SE, whereas self-emotion appraisal (SEA) showed a negative relationship. The fourth dimension, use of emotion (UOE), was not associated with SE. When controlling for gender and marital status, only OEA and ROE remained associated to SE. Additionally, a comparison of estimation techniques revealed that WLSMV provided a better model fit than maximum likelihood estimation (MLE) for latent constructs measured with Likert-scale items. These findings have important implications for university management and educators seeking to understand and enhance students’ self-efficacy in the Nepali context.